Documenting outdoor activity and travel behaviour in persons with neurological conditions using travel diaries and GPS tracking technology: a pilot study in multiple sclerosis. (24th January 2013) - Neven, An; Janssens, Davy; Alders, Geert; Wets, Geert; Wijmeersch, Bart Van; Feys, Peter
Abstract: Objective : Persons with multiple sclerosis (PwMS) experience several physical and cognitive problems which can influence their travel behaviour. This study aimed to document the number of activities, the activity type and the transport mode of the related trips that are daily made by PwMS. Their outdoor activity and travel behaviour was studied in relation to disease-related disability. Methods : Thirty six PwMS (Expanded Disability Status Scale, EDSS, 1.5–8.0, age 27–63) and 24 healthy controls (age 25–62) were studied, using activity-related travel diaries and GPS tracking devices. Information about overall disability characteristics was gained by standard clinical tests and questionnaires. PwMS were further divided in three subgroups based on EDSS cut-off scores 4.5 and 6.5. Results : Persons with mild ambulatory dysfunction (EDSS 1.5–4.0, n  = 17) showed similar travel characteristics to healthy controls, with few restrictions during travelling. Statistically significant changes in activity and travel behaviour were detected in the moderate (EDSS 4.5–6.5, n  = 8) and severe MS subgroups (EDSS > 6.5–8.0, n  = 11) compared with healthy controls: driving independently became less frequent, significant more trips were made with company and the duration of performed activities had increased. Conclusion : The combination of self-reported travel diaries and objective GPS loggers offered detailed information about the actual outdoor travel behaviour of PwMS, which was significantly changed in PwMS with EDSS greater than 4. Implications for Rehabilitation: Activity and travel behaviour changes significantly in persons with multiple sclerosis (MS) with moderate to severe disability (EDSS greater than 4). Behavioural therapy could help to develop better coping and problem-solving skills to overcome anxiety in the making of trips by persons with MS with a mild severity. Enhancing community environments could serve as a promising approach to increase the outdoor participation of persons with (more severe) impairments.